1995
DOI: 10.1182/blood.v85.3.765.bloodjournal853765
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive interleukin-6 and acute phase proteins as prognostic factors in multiple myeloma. Finnish Leukemia Group

Abstract: High serum level of bioactive interleukin-6 (IL-6) is regarded as a predictor of poor prognosis in multiple myeloma (MM). On the other hand, the reported levels of immunoreactive IL-6 have been highly variable, and the prognostic value of immunoreactive IL-6 in MM is not clear. We have analyzed the prognostic significance of serum immunoreactive IL-6, as measured by a sensitive immunosorbent assay, in 210 patients with newly diagnosed MM subsequently treated with intermittent melphalan and prednisone. The seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 33 publications
8
65
1
2
Order By: Relevance
“…These results prompted us to speculate that elevated serum IL-6 levels may inhibit the Th1 immune response in MM patients. Increased serum levels of IL-6 have been documented in active MM patients [32]. However, the data are discordant due to differences in assay sensitivity [38].…”
Section: Discussionmentioning
confidence: 86%
“…These results prompted us to speculate that elevated serum IL-6 levels may inhibit the Th1 immune response in MM patients. Increased serum levels of IL-6 have been documented in active MM patients [32]. However, the data are discordant due to differences in assay sensitivity [38].…”
Section: Discussionmentioning
confidence: 86%
“…The patients were either treatment-naive, had received treatment before or were undergoing treatment when serum IL-6 was measured. Secondly, cut-off values for the upper normal IL-6 level in serum were either not given (Brown et al, 1991;Thaler et al, 1994;Greco et al, 1994;Kyrtsonis et al, 1996) or ranged widely from 3´2 pg/ml (Pelliniemi et al, 1995) to 3300 pg/ml (Tienhaara et al, 1994). Each study reported a different range of values, even for normal controls (Table III).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is expressed by myeloma cells and mediates autocrine growth (see Kishimoto et al, 1995). High serum levels of IL-6 and CRP or 1AT as its surrogates have been associated with poor prognosis in MM patients (Pelliniemi et al, 1995). In addition, the raised concentration of sIL-6R is an independent prognostic factor and if both IL-6 and sIL-6R levels are elevated the patients have an even worse prognosis (Pulkki et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Raised serum concentrations of IL-6 as well as its surrogates, C-reactive protein (CRP) and 1-antitrypsin (1AT), are associated with poor prognosis in patients with multiple myeloma (MM) (Bataille et al, 1992;Pelliniemi et al, 1995). As OSM may simulate the effects of IL-6 we studied serum OSM concentration in relation to prognostic factors in 40 newly diagnosed MM patients.…”
mentioning
confidence: 99%